2012
DOI: 10.1111/j.1475-5661.2012.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity and the topologies of infected life: from borderlines to borderlands

Abstract: Biosecurity, as a response to threats from zoonotic, food‐borne and emerging infectious diseases, implies and is often understood in terms of a spatial segregation of forms of life, a struggle to separate healthy life from diseased bodies. While an ensuing will to closure in the name of biosecurity is evident at various sites, things are, in practice and in theory, more intricate than this model would suggest. There are transactions and transformations that defy easily segmented spaces. Using multi‐species eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
0
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(220 citation statements)
references
References 54 publications
(59 reference statements)
3
209
0
8
Order By: Relevance
“…Prainsack and Buyx's (2012) discussion of solidarity as an emerging principle in public health ethics stems from an extensive literature review and from treating biobanking, pandemics, and lifestyle-related diseases as case studies (Prainsack & Buyx, 2012). These three cases each have One Health valences, which have been explored elsewhere (e.g., French & Mykhalovskiy, 2013;Haraway, 2008;Hinchliffe et al, 2013). Prainsack and Buyx (2012), however, treat multi-species coexistence matter-of-factly.…”
Section: Solidarity Amongst Humans and More-than-human Solidaritymentioning
confidence: 99%
“…Prainsack and Buyx's (2012) discussion of solidarity as an emerging principle in public health ethics stems from an extensive literature review and from treating biobanking, pandemics, and lifestyle-related diseases as case studies (Prainsack & Buyx, 2012). These three cases each have One Health valences, which have been explored elsewhere (e.g., French & Mykhalovskiy, 2013;Haraway, 2008;Hinchliffe et al, 2013). Prainsack and Buyx (2012), however, treat multi-species coexistence matter-of-factly.…”
Section: Solidarity Amongst Humans and More-than-human Solidaritymentioning
confidence: 99%
“…In answering this question, I consider the complexities that guide the normalisation of security (Amoore, 2009), but also the relations that sustain and challenge how security in performed. Here, I draw on topological 'sensibilities' (Hinchliffe et al, 2013) to explore the contested and uncontested relations in spaces observed and controlled by CCTV cameras. The premise, as with much of the topological work, is the spatial/temporal dynamics when objects or devices bind relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The distance traversed by the SAR was used to demonstrate the multifarious ways in which five topologies of surveillant relations illuminate how these 36 relations are put into practice. CCTV data remains the constant, but, as Latham (2011) or Hinchliffe et al (2013) would have it, in topological terms it is not the object or the distance between things that is important, rather it is the relations that bind which are.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet the significance of nonhuman pathogens should not be reduced to a chain-of-causation way of conceptualizing disease onset. Rather, systemic relationships drive the incidence of infectious diseases, including zoonoses (Green 2012, Hinchliffe et al 2012, Mendelsohn 1998. Furthermore, institutionalized ways of thinking about and acting upon pathogens reflect systems of thought and their historical development (Lakoff 2008, Weir andMykhalovskiy 2010).…”
Section: Humanist Values In a More-than-human Worldmentioning
confidence: 99%